The Federal Supreme Court and the regulation of the social media: the metalanguage adopted by the court in the decision of the ADPF 130/DF - Cajú, Oona de Oliveira (Law, State and Telecommunications Review, 2017)
Purpose ”“ This article analyzes the votes uttered by the Federal Supreme Court justices at the trial of ADPF 130/DF, in which it was denied value to the Press Law. It also tackles the reasoning behind the Court’s decision, which clarifies its conception of regulation of the social media.Methodology/approach/design ”“ The first section of the article presents the most influent theoretical paradigms on the social media regulation. The second section confronts them with votes presented at the trial of the ADPF 130/DF and extract the guiding conceptual syntheses of the justices, identifying the regulatory paradigm of communicational field to which they align themselves. Findings ”“ It was possible to identify that the libertarian paradigm of free flow of informartion is the predominant mindset guiding the rulings concerning social media in the Federal Supreme Court.